A contextual approach to information privacy research. (16th April 2019) - Wu, Philip Fei; Vitak, Jessica; Zimmer, Michael T.
Abstract : In this position article, we synthesize various knowledge gaps in information privacy scholarship and propose a research agenda that promotes greater cross‐disciplinary collaboration within the iSchool community and beyond. We start by critically examining Westin's conceptualization of information privacy and argue for a contextual approach that holds promise for overcoming some of Westin's weaknesses. We then highlight three contextual considerations for studying privacy—digital networks, marginalized populations, and the global context—and close by discussing how these considerations advance privacy theorization and technology design.